Effect of Fiberglass Layer Number on the Mechanical Properties of Composites Fabricated Using the Vacuum-Assisted Resin Infusion (VARI) Method - Hanifah, Istiara Rizqillah; Putra, Oji Kuncoro Darma; Sipahutar, Wahyu Solafide; Phasa, Agita (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2025)
Composite materials are engineered by combining two or more constituents to obtain improved mechanical performance. In this study, the effect of fiberglass layer number (2 and 3 layers) on the mechanical properties of composites was investigated. The specimens were fabricated using the Vacuum-Assisted Resin Infusion (VARI) method, and mechanical tests were conducted based on ASTM D3039 (tensile) and ASTM D790 (flexural) standards. The 3-layer specimen (A2) exhibited the highest tensile strength of 223.33 MPa and flexural strength of 845.54 MPa, compared to 179.73 MPa and 828.35 MPa in the 2-layer specimen (A1), respectively. In addition, the 3-layer composite showed greater stiffness with an elastic modulus of 612.76 GPa in bending and 1.41 GPa in tension. These results confirm that increasing the number of fiberglass layers enhances the composite's mechanical strength, due to better load distribution and improved interfacial bonding.